2012
DOI: 10.5515/jkiees.2012.12.4.271
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extremely Low Frequency Magnetic Fields on Gene Expression in Human Mammary Epithelial MCF10A Cells

Abstract: The effects of extremely low frequency magnetic fields (ELF-MFs) on physiological processes at the cellular level remain unclear despite a number of studies. To investigate the effects of ELF-MFs on gene expression, we exposed human mammary epithelial MCF10A cells to fields of 1 mT magnetic flux density at 60 Hz for 4 and 16 h and measured the transcriptional responses of 24,000 genes using Illumina microarrays. In three independent experiments, we found no statistically significant alteration of expression le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Loberg et al [] reported that no genes were differentially expressed in each of three independent exposures in normal and transformed human mammary epithelial cells exposed to 0.01 or 1.0 mT ELF‐MF for 24 h. Ishido et al [] found that expression of nine oncogenes was significantly altered in MCF7 cells by exposure to 50 Hz ELF‐MF at 0.1 mT for 1 week. We previously reported that exposure of MCF10A cells to 1 mT ELF‐MF did not result in differential gene expression [Hong et al, ]. In the present study, we identified and validated change in expression of the PMAIP1 gene in response to ELF‐MF exposure using high throughput and non‐high throughput techniques in MCF7 cells.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Loberg et al [] reported that no genes were differentially expressed in each of three independent exposures in normal and transformed human mammary epithelial cells exposed to 0.01 or 1.0 mT ELF‐MF for 24 h. Ishido et al [] found that expression of nine oncogenes was significantly altered in MCF7 cells by exposure to 50 Hz ELF‐MF at 0.1 mT for 1 week. We previously reported that exposure of MCF10A cells to 1 mT ELF‐MF did not result in differential gene expression [Hong et al, ]. In the present study, we identified and validated change in expression of the PMAIP1 gene in response to ELF‐MF exposure using high throughput and non‐high throughput techniques in MCF7 cells.…”
Section: Discussionsupporting
confidence: 61%
“…We next wanted to investigate modification of gene expression profile in MCF7 cells, which showed a reduction in cell numbers following ELF‐MF exposure. As we previously failed to detect a modification in the gene expression profile of MCF10A cells exposed to fields of 1 mT magnetic flux density at 60 Hz for 16 h [Hong et al, ], in this study, we chose MCF7 cells and adopted a 2 mT maximum ELF‐MF intensity in our exposure chamber to identify genes that clearly exhibited variable expression. Consistent with results observed following exposure to 1 mT ELF‐MF, exposure to 2 mT ELF‐MF resulted in lower numbers of cells (Fig.…”
Section: Resultsmentioning
confidence: 99%